(untitled) (Journal of Statistics on Health Decision, 2023)
Objective: To contribute to the translation of the self-administered ALSFRS-R - European Portuguese version (ALSFRS-R: EP), and to analyse its reliability to enable its use by ALS patients in Portugal. Methods: The study was developed in 3 phases. Phase 1: Translation and cultural adaptation of the self-administered ALFRS-R; Phase 2: Content validation by study participants; Phase 3: Exploratory factor analysis (EFA), analysis of its internal consistency and test-retest reliability. Results: According to a panel of experts (N=6), a CVI of 100% were obtained for all ALSFRS-R: EP items. A sample of 18 people with ALS (13 male) fulfilled the test and evaluated its items regarding its clarity, comprehension, difficulty, and relevance, obtaining values varying from 8.6 and 8.9, 8.7 and 8.9, 8.5 and 8.8, and 8.5 and 8.9, respectively. The EFA revealed three factors representing the following domains: (1) bulbar function; (2) fine and gross motor function; and (3) respiratory function. The instrument total score and its subscales presented good internal consistency (Cronbach’sα: ranging from 0.72 to 0.92 in the test; from 0.70 to 0.95 in the retest) and good to excellent test-retest reliability (Kendall tau: ranging from 0.58 to 0.99). Considering the scale total score for the test, no statistical differences were observed between females and males nor between bulbar ALS and medullar ALS. The correlation between the total score and age showed to be significant and negative (-0.53). Conclusions: The Self-Administered ALSFRS-R: EP version was successfully translated, validated, and presented good to excellent reliability results, with similar EFA structure to other studies. It will allow its use by European Portuguese ALS patients, enabling their health professionals to monitor the disease progression at home.